Ex-gaussian model reveals performance biomarkers related to emotion-cognition interaction during public speaking anxiety - Feroz, Farah Shahnaz; Andrea Cheang, Sheau Shyuan; Subramaniam, Siva Kumar (Universiti Kebangsaan Malaysia, 2023)
This research is to compare the reaction time (RT) of low public speaking anxiety (LPSA) and high (HPSA) individuals using Ex-Gaussian modelling technique to investigate behavioural abnormalities in individuals with PSA. Despite the fact that one out of every four individuals worldwide experiences PSA, there remains a notable lack of research on this condition. With that, the RT performance biomarker of PSA is still unclear. This study observed the correlation between Ex-Gaussian parameters and the level of trait anxiety in 12 subjects with LPSA and 12 subjects with HPSA in an emotion-cognition Eriksen-Flanker (ECEF) experiment. Results revealed that sigma (